Kinetics of hydrogenation of aqueous levulinic acid over bimetallic Ru-Ni/MMT catalyst - Kasar, Gayatri B.; Medhekar, Rucha S.; Bhosale, P. N.; Rode, V, Chandrashekhar (Industrial & Engineering Chemistry Research, 2019)
gamma-Valerolactone is one of the value-added products obtained from levulinic acid hydrogenation, having tremendous applications in fuels and chemicals. In this work, several monometallic and bimetallic compositions of Ru and Ni were prepared and evaluated for levulinic acid hydrogenation in an aqueous medium. The optimum composition of 0.5 wt % Ru and 5 wt % Ni on MMT was found to achieve 91% levulinic acid conversion with complete selectivity to gamma-valerolactone within 5 h at 220 degrees C and 250 psig H-2 pressure. XPS and H-2-TPR studies clearly showed that the electronic interactions between Ru-Ni leading to the synergism enhanced the catalytic efficiency of the Ru-Ni bimetallic catalyst. The average metal particle size by HRTEM was found to be in the range of 1.5-4.5 nm, having mixed cubic, oval, and spherical morphology, dispersed on the surface as well as within the layers of MMT. NH3-TPD showed a higher acidity due to both Lewis and Bronsted sites of the 0.5 wt % Ru-5 wt % Ni/MMT catalyst than individual MMT and monometallic catalysts. The presence of higher Lewis acidic sites preferred selective formation of GVL. Reaction kinetics was studied to propose the rate equation for this reaction based on which a plausible reaction pathway is proposed involving a first step dehydration of levulinic acid to an alpha-angelica lactone intermediate which then undergoes hydrogenation by dissociatively adsorbed H-2 to form gamma-valerolactone. The stability of our catalyst was proved by its recycle studies as well as by a hot filtration test.